A novel fertility-sparing nanocomposite for endometriosis treatment via oxidative stress and inflammation alleviation - Wenwen Liu; Jie Shen; Jiaqi You; Tao Wang; Pusheng Yang; Yaxin Miao; Xiaotong Peng; Yimin Yu; Chengyu Liu; Ang Li; Jing Sun (Materials Today Bio)
Endometriosis, an estrogen-dependent inflammatory disorder prevalent in reproductive-age women, is characterized by the growth of endometrial-like tissue outside the uterine cavity, leading to chronic pain and infertility. Current therapeutic strategies primarily focus on lesion removal and pain alleviation, often at the cost of compromising ovarian function and natural conception. Herein, we engineered a nanocomposite with polydopamine and dydrogesterone for precise and gentle endometriosis treatment while protecting ovarian function and fertility. It combines polydopamine 's anti-inflammatory and antioxidant capacities with dydrogesterone's ectopic lesion regression capability while maintaining physiological ovulation. To enhance the lesion-specific delivery, the nanocomposite was functionalized with polyethylene glycol and laminin. Through in vitro and in vivo studies, we demonstrate that the nanocomposites exhibit potent antioxidant and anti-inflammatory properties, coupled with targeted delivery to ectopic endometrial cells. The nanocomposites effectively accumulate in ectopic lesions, modulate macrophage polarization, and promote the atrophy and clearance of ectopic endometrial tissue. Importantly, this therapeutic approach preserves ovarian reserve function and fertility, showing no significant adverse effects on ovarian health. In summary, we present an innovation non-surgical therapeutic strategy for endometriosis that demonstrates both safety and efficacy while preserving ovarian reserve function and fertility potential.